Aging, social inequality, and public policy - Pampel, Fred C. (Thousand Oaks Pine Forge Press, 1998)
Fred C. Pampel describes how age combines with other components of inequality by comparing the influence of group membership on social inequality before and after the life course transition to old age. He looks at the differences in public policy and how age inequality -- more than the other sources of inequality -- relates closely to government policies and studies other societies in which both age group differences and overall inequality differ from those in the United States. Pampel makes a comparison of the United States with other nations a central component of the book, providing greater understanding of the larger forces that shape old age.-- Amazon.
1. Images of old age -- 2. Public policy in old age -- 3. Class differences before and during old age -- 4. Race, ethnic, and gender differences in old age -- 5. Old age support in comparative perspective -- 6. Inequality across age groups and generations.
Includes bibliographical references (p. 153-166) and index.
PI-8277 donated by Department of Global Development Cornell University Ithaca.
Keywords: Equality; Old age assistance; Equality -- United States; Old age assistance -- United States; Older people -- Government policy; Older people -- Social conditions; Older people -- Government policy -- United States; Older people -- United States -- Social conditions